Fractional PID Control of an Experimental Servo System - Barbosa, Ramiro (2019)
This paper investigates the application of fractional-order PID controllers in the velocity control of a servo system. The servo system is controlled by using a real-time digital control system based on MATLAB/Simulink tools. Experimental responses are presented and analyzed, showing the effectiveness of the proposed fractional-order algorithms. Comparison with classical PID controllers is also investigated.